Back Cover: Magnetism in Lithium–Oxygen Discharge Product (ChemSusChem 7/2013). Issue 7 (4th July 2013) - Lu, Jun; Jung, Hun‐Ji; Lau, Kah Chun; Zhang, Zhengcheng; Schlueter, John A.; Du, Peng; Assary, Rajeev S.; Greeley, Jeffrey; Ferguson, Glen A.; Wang, Hsien‐Hau; Hassoun, Jusef; Iddir, Hakim; et al.
<x xml:space="preserve">Abstract</x> The Back Cover Image shows an illustration of lithium peroxide nanoparticles growing on a carbon surface. These nanoparticles, reported by Curtiss et al. in their publication on page 1196 show an electronic spin density on the nanoparticle that has been revealed by a combination of experiment and theory. Dr. Hakim Iddir, Dr. Kah Chun Lau, and John Russell contributed considerably to the preparation of this image.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>